POLITICAL CHARACTERISTICS AND PUBLIC FINANCIAL PERFORMANCE UNDER THE LIGHT OF THE POLITICAL CYCLES THEORY - Fiirst, Clóvis; Santos, Alexandre Corrêa dos; Rodrigues Junior, Moacir Manoel; Zonatto, Vinícius Costa da Silva (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
One of the main indicators of the effectiveness of public policies is budget execution, which should reflect social interests in the qualitative and quantitative aspects and be implemented in harnessing resources in a transparent and sustainable way. However, studies show that public financial performance is affected by political cycles, which indicates political and democratic backwardness. This descriptive, documental and quantitative study aims to verify the influence of political characteristics on the financial performance of the municipalities of Paraná, under the lens of the theory of political cycles. Data, from the period 2013 to 2016, of 377 municipalities were collected from the TCE-PR, TSE and IBGE sites and were analyzed by multiple regression with panel data. The results show that the electoral year positively influences the financial performance, however this relationship is negative in periods when government is changed.